PENGARUH TINGKAT PELAYANAN TERHADAP KEPUASAN NASABAH BANK BNI UNIT KOLAKA - Sitti Fitri; Muhammad Zakariah; Muhammad Askari Zakariah (IAI Al-Mawaddah Warrahmah Kolaka, 2018)
Customer complaints indicate that the level of customer service is still lacking, where customers feel more secure and comfortable transacting via SMS banking than having to come directly to the Bank. This type of research is quantitative research using the SPSS method using primary data from the results of a questionnaire on a sample of 35 respondents. The sampling method is questionnaire distribution. The method of analysis uses the method of reability and correlation. Reability analysis shows that the data is valid. Because, alpha > 0.60 and the correlation analysis shows that the results of empathy and responsiveness are very directly related and can affect the interest of customers to transact at Bank BNI.